Wordpress basics for photographers. Part 2 - Concepcion, Rafael; Safari eBooks ([S.l. : Kelbytraining], 2010)
"Once you have a basic Wordpress site up to show your photography, there are a few things you can do to spice it up and make it look more professional. RC Concepcion takes you through the things he likes to use to make the most of using Wordpress for photography"--Resource description page (viewed April 29, 2010).
System requirements: Adobe Flash Player, version 8 or higher; or QuickTime Player, version 7.2 or higher; or Windows Media Player, version 11 or higher.
Title, presenter, and date from resource description page (viewed April 29, 2010).
Publisher from end credits.
Keywords: WordPress (Electronic resource); Photography -- Digital techniques; Electronic books